A Study on the Perception of Rural Customers Towards Banking Services in Punjab - Singh, Vajinder Pal; Lamba, Bhuvan (Indian Journal of Finance, 2015)
The necessity of financial inclusion is urgent, particularly in the rural hinterlands, where the vast majority of the population resides. However, these areas continue to remain excluded from formal banking facilities, despite various attempts made by the government, policy makers, and also credit institutions. The main objective of the present study was to study the perceptions of the rural customers towards banking services in Punjab and also to calculate the mean gap between customers’ expectations and perceptions towards banking services in rural areas (with specific reference to Punjab). The current study was aimed at evaluating the service quality of banks in the rural areas. To support the objectives of the study, SERVQUAL technique was adopted by using 20 variables grouped under five dimensions, Tangibility, Reliability, Responsiveness, Assurance, and Empathy using the 5 point likert scale.